Development of the potato cryocollection preserved in the VIR cryobank - O. S. Efremova; N. N. Volkova; D. A. Rybakov; O. V. Lisitsyna; P. V. Ozerski; Т. A. Gavrilenko (Труды по прикладной ботанике, генетике и селекции)
Background. The article presents the results of the studies carried out within the framework of a complex program for the long-term conservation of genotyped accessions of advanced potato cultivars in the cryobank of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). These accessions are genetically identical to the nomenclature standards of the corresponding cultivars.Materials and methods. The research material included 24 accessions from the in vitro collection of VIR, corresponding to the nomenclature standards of Russian potato cultivars developed in different breeding centers of the Russian Federation. Cryopreservation was carried out using the droplet vitrification method, several stages of which were modified in the Department of Biotechnology of VIR.Results and discussion. The frequency of post-cryogenic regeneration for the analyzed 24 cultivars in control variants with short-term immersion of explants in liquid nitrogen varied from 20 to 47.3%, and in 9 accessions it exceeded 39% – the current level of reliable long-term preservation of samples in cryobanks. The data of the statistical analysis failed to reveal a significant effect of the genotype or the calendar dates of different experiment replications on the regeneration ability. These 24 accessions were added to the potato cryocollection stored in the VIR cryobank. An analysis of the composition and structure of VIR’s potato cryocollection, which currently includes 140 accessions, is presented.